2010
DOI: 10.3390/md8072021
|View full text |Cite
|
Sign up to set email alerts
|

Palytoxin and Analogs: Biological and Ecological Effects

Abstract: Palytoxin (PTX) is a potent marine toxin that was originally found in soft corals from tropical areas of the Pacific Ocean. Soon after, its occurrence was observed in numerous other marine organisms from the same ecological region. More recently, several analogs of PTX were discovered, remarkably all from species of the dinoflagellate genus Ostreopsis. Since these dinoflagellates are also found in other tropical and even in temperate regions, the formerly unsuspected broad distribution of these toxins was reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 73 publications
1
83
0
1
Order By: Relevance
“…It was described that only the Japanese O. siamensis produces ostreocin [34], however other studies demonstrate that also Mediterranean O. siamensis synthesizes this toxin [13,35,36]. In addition PLTX or putative PLTX (depending on the author) have been identified in this specie [4,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was described that only the Japanese O. siamensis produces ostreocin [34], however other studies demonstrate that also Mediterranean O. siamensis synthesizes this toxin [13,35,36]. In addition PLTX or putative PLTX (depending on the author) have been identified in this specie [4,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Although the term PLTX-like compound is used to designate toxins coming from Ostreopsis spp. [13]. This controversy could be due to the lack of standards that prevent the clarification of the toxins produced by each strain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These are in temperature-, concentration-and solvent-dependent dynamic equilibrium, thus mimicking a kind of living system. 23 We have recently shown that the one-pot assembly of 3-methyl-7-methylene-1,5-diphenyl-6,8-dioxabicyclo[3.2.1]octane (having the pheromone frontaline scaffold) [24][25][26][27] from acetophenone 1a and acetylene 2a promoted by a KOH/DMSO suspension (Scheme 1) is accompanied by the formation of a minor product (yield < 1%), 3-benzoyl-2,4-dimethyl-1-phenyl-2-cyclopenten-1-ol (4a), a structural isomer of the bicyclic ketal 3a.…”
Section: Introductionmentioning
confidence: 99%